Electrokinetic‐Driven Fast Ion Delivery for Reversible Aqueous Zinc Metal Batteries with High Capacity. Issue 21 (21st April 2021) - Kim, Soohyun; Heo, Jiyun; Kim, Riyul; Lee, Ju‐Hyuk; Seo, Joowon; Yoon, Sehyuk; Lee, Hyomin; Kim, Sung Jae; Kim, Hee‐Tak
Abstract: Aqueous zinc (Zn) metal batteries (ZMBs) are considered a promising candidate for grid‐scale energy storage due to their freedom from fire hazards. However, a limited reversibility of Zn metal electrode caused by dendritic Zn growth has hindered the advent of high‐capacity Zn metal batteries (>4 mAh cm −2 ). Herein, it is reported that fast electrokinetic Zn‐ion transport extremely improves the Zn metal reversibility. It is revealed that a negatively charged porous layer (NPL) provides the electrokinetic Zn‐ion transport by surface conduction, and consequently impedes the depletion of Zn‐ion on electrode surface as indicated by numerical simulations and overlimiting current behavior. Due to the quick Zn‐ion delivery, a dendrite‐free and densely packed Zn metal deposit is accommodated inside its pores. With the introduction of the NPL, the cycling stability of Zn symmetric cell is enhanced by 21 times at 10 mA cm −2 /10 mAh cm −2 . Average Coulombic efficiency of 99.6% is achieved over 500 cycles for electrodeposition/stripping at 30 mA cm −2 /5 mAh cm −2 on NPL–Cu electrode. Furthermore, a high‐capacity Zn/V2 O5 full cell with the NPL exhibits an extraordinary stability over 1000 cycles at a capacity of 4.8 mAh cm −2 . Abstract : A negatively charged porous layer facilitates electrokinetic fast Zn‐ion delivery, impeding the depletion of Zn‐ion on the electrode surface. The quick Zn‐ion transport induces a dendrite‐free and densely packed Zn deposit inside its pore. The negatively charged porous polymeric Zn host extremely improves the Zn reversibility, and enables high‐capacity aqueous Zn metal batteries.